How to develop a professional portfolio - Campbell, Dorothy M (Pearson, 2006)
Includes bibliographical references and index.; This versatile and practical book helps pre- and in-service teachers create teaching portfolios to be used effectively in interviews and throughout their teaching careers. Portfolio development serves as a fair, authentic, broad-based, and impartial means of teacher assessment. The growing emphasis on creating and maintaining professional teaching portfolios enables pre-service and in-service teachers to play a more active role in charting their own professional growth and then demonstrating their competence and achievements. This manual provides clear, manageable, step-by-step guidelines and tips for professional portfolio development that can be followed by teachers at all stages of their careers